The Barrett‐associated variants at GDF7 and TBX5 also increase esophageal adenocarcinoma risk. (18th January 2016) - Becker, Jessica; May, Andrea; Gerges, Christian; Anders, Mario; Schmidt, Claudia; Veits, Lothar; Noder, Tania; Mayershofer, Rupert; Kreuser, Nicole; Manner, Hendrik; Venerito, Marino; Hofer, Jan‐Hinnerk; et al.
Abstract: Barrett's esophagus (BE) and esophageal adenocarcinoma (EAC) represent two stages within the esophagitis‐metaplasia‐dysplasia‐adenocarcinoma sequence. Previously genetic risk factors have been identified that confer risk to BE and EAC development. However, to which extent the genetic variants confer risk to different stages of the BE/EAC sequence remains mainly unknown. In this study we analyzed three most recently identified BE variants at the genes GDF7 (rs3072), TBX5 (rs2701108), and ALDH1A2 (rs3784262) separately in BE and EAC samples in order to determine their risk effects during BE/EAC sequence. Our data show that rs3072 at GDF7 and rs2701108 at TBX5 are also associated with EAC and conclude that both loci confer disease risk also at later stages of the BE/EAC sequence. In contrast, rs3784262 at ALDH1A2 was highly significantly associated with BE, but showed no association with EAC. Our data do not provide evidence that the ALDH1A2 locus confers equal risk in early and late stages of BE/EAC sequence. Abstract : The authors followed up SNPs at GDF7, TBX5, and ALDH1A2 that showed association with Barrett's esophagus (BE) in a previous study. The sample comprised 542 BE and 1106 esophageal adenocarcinoma (EAC) cases as well as 1602 controls. SNPs at GDF7 and TBX5 are also associated with EAC and thereby risk‐conferring also to later stages of the BE/EAC sequence. The variant at ALDH1A2 is associated with BE only, which indicates that this locus plays a more prominent role in early stages of the BE/EAC sequence.